This book bubbles over : from the ocean to Mars and everywhere in between - Nickum, Nora (Peachtree, 2025)
"This book really pops, full as it is of fascinating bubbles -- useful and entertaining, noisy and silencing, lifesaving and dangerous, microscopic and bigger than our solar system."--